2011
DOI: 10.1007/s10995-011-0908-4
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Education About Breastfeeding and Breast Pump Use: What Effect do they Have on Breastfeeding Duration? An Analysis of the Infant Feeding Practices Survey II

Abstract: To examine the association between breastfeeding duration and sources of education about breastfeeding and breast pumps. We analyzed data from the Infant Feeding Practices Survey II (n = 2,586), a national longitudinal consumer-based study. We used χ(2) and ANOVA to contrast categorical and continuous variables, respectively, and logistic regression to model the association between breastfeeding duration and sources of education about breastfeeding and breast pump use. In unadjusted results, multiple sources o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 24 publications
1
17
0
1
Order By: Relevance
“…Results of many studies have shown that active and direct participation of professional care-providers such as midwives in the breastfeeding training and consultation of mothers can have highly positive effects on the increase of exclusive breastfeeding process in term and preterm infants and its improvement [3539]. Based on Ahmed [40], breastfeeding training for the support of mothers having premature infants during the 3 months of follow-up can improve lactation performance and awareness of mothers about feeding infants on their milk.…”
Section: Discussionmentioning
confidence: 99%
“…Results of many studies have shown that active and direct participation of professional care-providers such as midwives in the breastfeeding training and consultation of mothers can have highly positive effects on the increase of exclusive breastfeeding process in term and preterm infants and its improvement [3539]. Based on Ahmed [40], breastfeeding training for the support of mothers having premature infants during the 3 months of follow-up can improve lactation performance and awareness of mothers about feeding infants on their milk.…”
Section: Discussionmentioning
confidence: 99%
“…Social support, such as education about breast pumps from friends and relatives, is positively associated with longer durations of feeding HM [28]. Mothers’ reported reasons for considering stopping, such as feeling tired from balancing pumping, cleaning pump supplies, and taking care of their infants, point to ways in which their partners and families may offer support.…”
Section: Discussionmentioning
confidence: 99%
“…However, Chen et al recently reported that receiving breast pump education from a physician or physician assistant was a risk factor for shorter breastfeeding duration, while receiving breast pump education from a class or support group was a protective factor associated with longer breastfeeding duration. 70 These associations could be attributable to differences in the quality of counseling received from these different sources, but the study’s results might also be attributable to the fact that breast pump teaching by a physician is a marker of learning breast pumping as an inpatient, which, as discussed above, may not be the best time to learn pumping.…”
Section: Mother’s Experiences Of Milk Expressionmentioning
confidence: 91%